2014
DOI: 10.1007/s00431-014-2268-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin levels and iron metabolism in obese children with and without fatty liver: case–control study

Abstract: Hepcidin levels were significantly higher in obese children with NAFLD than those without NAFLD. Obese children with NAFLD should receive attention regarding iron metabolism disorders. Serum hepcidin could be a marker of iron metabolism status and NAFLD in these groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…The expression of hepcidin, for example, is also stimulated by adipokines [40, 42]. Hepcidin levels were significantly higher in obese children with NAFLD than in those without NAFLD [43]. According to the present study, therefore, changes in the hepcidin regulation would be possible but should be the focus of future investigations.…”
Section: Discussionmentioning
confidence: 74%
“…The expression of hepcidin, for example, is also stimulated by adipokines [40, 42]. Hepcidin levels were significantly higher in obese children with NAFLD than in those without NAFLD [43]. According to the present study, therefore, changes in the hepcidin regulation would be possible but should be the focus of future investigations.…”
Section: Discussionmentioning
confidence: 74%
“…Several human studies have elucidated the role of hepcidin in iron overload and chronic liver disease [21,22], but its effect on NAFLD is controversial. In the study by Auguet et al [11], the plasma levels of hepcidin among women with morbidly obesity were not significantly different between NAFLD patients and those with normal liver; however, Demircioğlu et al [16] reported that among children with obesity, hepcidin levels were significantly higher in NAFLD patients than in controls. In the present study, we found that serum hepcidin levels were not associated with NAFLD risk, but may have augmented the risk effect of central obesity on NAFLD (p = 0.04).…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…Hepcidin is the principal regulator of systemic iron homeostasis, secreted mainly by hepatocytes in response to iron perturbations, inflammation, and hypoxia [15]. However, the role of hepcidin in the pathogenesis of NAFLD is controversial [11,16,17]. The reasons for these inconsistent results are unclear, but may relate to patient selection/study design, or competing factors that may influence serum levels of ferritin and hepcidin.…”
Section: Introductionmentioning
confidence: 99%
“…After applying the inclusion and exclusion criteria, a total of 26 original studies were ultimately included in the meta‐analysis (Fig. ), including 21 cross‐sectional studies and 5 case–control studies ; no cohort studies were include in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13,393 overweight and/or obese subjects and 26,621 non‐overweight subjects were included in these 26 studies. Fifteen studies reported serum iron levels , 10 reported TS% , 15 reported serum ferritin and 4 reported sTfR . Fifteen studies evaluated the risk of developing ID among overweight/obese populations , and four studies evaluated the risk of developing IDA .…”
Section: Resultsmentioning
confidence: 99%